2004
DOI: 10.1016/j.visres.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the effects of slant and texture type on slant-from-texture

Abstract: We measure the performance of five subjects in a two-alternative-forced-choice slant-discrimination task for differently textured planes. As textures we used uniform lattices, randomly displaced lattices, circles (polka dots), Voronoi tessellations, plaids, 1/f noise, "coherent" noise and a leopard skin-like texture. Our results show: (1) Improving performance with larger slants for all textures, (2) and some cases of "non-symmetrical" performance around a particular orientation. (3) For orientations sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…The variations in physical slant accounted for 63.2% of the total variance in the observers' judgments. Given that similar past research has shown significant underestimation (e.g., Gibson, 1950b;Rosas et al, 2004;Saunders, 2003), it is interesting that our observers did not exhibit underestimation. In contrast, our observers' judgments of slant were accurate for all three of the natural textures (marble, granite, and pebble tex- interaction for the older observers and no such interaction for the younger observers) was responsible for the observed age slant texture interaction.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The variations in physical slant accounted for 63.2% of the total variance in the observers' judgments. Given that similar past research has shown significant underestimation (e.g., Gibson, 1950b;Rosas et al, 2004;Saunders, 2003), it is interesting that our observers did not exhibit underestimation. In contrast, our observers' judgments of slant were accurate for all three of the natural textures (marble, granite, and pebble tex- interaction for the older observers and no such interaction for the younger observers) was responsible for the observed age slant texture interaction.…”
Section: Resultssupporting
confidence: 66%
“…The observers' judgments of slant in Experiment 1 (see Figure 3) were generally accurate: Our observers did not exhibit the underestimation that has been obtained in many previous studies (see, e.g., Andersen et al, 1998;Rosas et al, 2004;Saunders, 2003;Todd et al, 2005). Given that our surfaces were physically slanted in depth (instead of being simulated computationally and then displayed on a frontoparallel monitor or projection screen), it is possible that other monocular factors, such as accommodative blur (Ciuffreda, Wang, & Vasudevan, 2007;Frisby, Buckley, & Horsman, 1995;Watt, Akeley, Ernst, & Banks, 2005), contributed to the accurate performance of our observers in Experiment 1.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…In a recent paper Rosas et al 8 showed that different texture types elicit different performance in a slantdiscrimination task. This effect was observed by measuring the discrimination performance of the slant of a textured plane at different slant levels.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of variation 'from point to point in the texture is directly related to the distance from the viewer' (Rosas et al, 2004). This cue will improve not only the depth perception but also the surface orientation in the case of surfaces slanted in depth.…”
Section: Textural Gradient In Renderingmentioning
confidence: 99%